KAJIAN: KHASIAT DAN KEAMANAN STEVIA SEBAGAI PEMANIS PENGGANTI GULA - Raini, Mariana; Isnawati, Ani (Badan Penelitian dan Pengembangan Kesehatan, 2011)
The increasing of diabetic prevalence encouraged scientists to discover sweetener as sugar substitution. Stevia is a perenial shrub (known as Stevia rebaudiana) of the aster family that has been used for hundred of years to sweetening. Stevia is a natural, non caloric, sweet tasting plant known for its pleasant sweet taste without leaving bitter aftertaste. The leaves contain primarily stevioside and rebaudioside. Both have potential for antihyperlicemic and blood pressure lowering effect. Besides its empirical long-use without any reported toxicity in Latin America and Asia, Japan also enhanced its widespread use. Negative side effects of Stevia has not been seen yet. Stevioside and rebaudioside are not genotocsic in vitro or in vivo in animal models and the genotocicity of steviol and some of its oxidative derivats in vitro are not expressed in vivo. (The study is an assessment derived from 30 of the report studies/review collected from international journals). The objective is to evaluate the biochemical, to study the effect and safety of stevia herb as well as to support its use as sugar substitution particularly for diabetic patients. ARTIKEL Abstrak Meningkatnya prevalensi diabetes mendorong para ilmuwan untuk menemukan pemanis sebagai pengganti gula. Stevia adalah semak perenial (dikenal dengan Stevia rebaudiana) bagian dari keluarga aster yang te;ah digunaka selama ratusan tahun sebagai pemanis. Stevia alami, non kalori, tanaman yang dikenal dengan rasa manisnya tanpa meninggalkan rasa pahit jika dicicipi. Daunnya mengandung stevioside dan rebaudioside. Keduanya memiliki antihpyperlicemic dan berpotensi menurunkan tekanan darah. Efek samping dari stevia belum ada. (Penelitian ini merupakan penialaian yang berasal dari 30 laporan studi/review yang dikumpulkan dari jurnal internasional). Tujuannay adalah untuk mengevaluasi biokimia, untk mempelajari efek dan kemanan Stevia serta mendukung penggunanannya sebagai pengganti gula terutama untuk pasien diabetes.